До питання атрибуції бушанського наскельного рельєфу (аналіз обрамленої таблиці з написом) - Забашта, Р. (Студії мистецтвознавчі, 2009)
Here we have an overview of versions of graphic symbols’ recognition and the superscription interpretations by various authors, notably: А. Spitsyn, who interpreted the superscription as a Greek Medieval text; V. Danylenko, who dated the superscription to the 9th century, before the appearance of the Cyrillic characters; А. Formozov, who suggested the text to have appeared at the beginning of the 16th century; V. Berezyak, who recognized the superscription as a Polish text (1524). Earlier the author of the article suggested that the tablet contained the 2nd verse of the 41st psalm. Bad condition of the superscription caused many views. The author offers a few guidelines to interpret all versions and presents a new correct recognition and interpretation of the superscription.